Command and Control Information Systems for Military Applications - Todorović, Branislav; Vasić, Zoran; Ostojić, Andrija; Sretenov, Saša; Kopta, Aleksandar; Lazović, Aleksandar; Paunović, Lazar; Đilas, Veljko; Delić, Miloš; Delić, Mirko (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: A command and control information system (C2IS) is a technical system designed to provide decision makers with the information they need to plan, coordinate, and manage operations. It consists of hardware and software, and includes a specialized set of tools and processes that aim to ensure the timely and accurate flow of information. C2IS can be intended for military applications, public safety, and corporate management. The paper presents the historical development of military C2IS. Examples of modern C2IS of some technologically advanced countries are given, such as the USA (NATO), the Russian Federation, the People’s Republic of China, India, the United Kingdom, France and Israel.